(untitled) (Journal of the College of Basic Education, 2024)
The history of human society preserves an important, special and distinguished role for the intellectual and intellectuals in our society and then in the process of building, constructing and flourishing human civilizations and in alerting them to their decline and deterioration and their sayings. Culture is intelligence, strength of personality, independence of opinion, and correct information